Evaluasi Penggunaan Java 2D dalam Pengembangan Aplikasi Animasi 2D - Safitri, Luthfi; Fachmi, Achmad; Nugraha Reynaldi, Aditya Dwi; Syahira, Astrit Salwa (shofanah Media Berkah, 2024)
2D animation is now widely used for various applications such as games, multimedia and simulations. Java 2D is a technology choice for creating interactive 2D animations. However, there is still little comprehensive research regarding evaluating the strengths and weaknesses of Java 2D as a 2D animation development platform. Research methods include research stages, quantitative and qualitative analysis techniques. This research aims to evaluate the use of Java 2D in developing 2D animation applications. It is hoped that this research can recommend the use of Java 2D.